Mechanical properties and water absorption of cement composites with various fineness and contents of waste brick powder from C&D waste. (November 2020) - Ma, Zhiming; Tang, Qin; Wu, Huixia; Xu, Jianguang; Liang, Chaofeng
Abstract: The use of waste brick powder (WBP) as supplementary cementitious material (SCM) provides an effective approach to reclaiming construction and demolition (C&D) waste. This research shows the evolution of preparing eco-friendly mortar with various fineness levels and replacement ratios of WBP from waste brick in C&D waste. Due to the pozzolanic activity and filler effect of WBP, incorporating an appropriate content and fineness of WBP refines the pore network of cementitious materials, while the number of hydration products decreases with WBP addition. With WBP incorporation, the water demand increases and mixture slump decreases, while the use of WBP improves the drying shrinkage resistance. The pozzolanic activity increases with increasing WBP fineness; when the WBP fineness is higher than the cement fineness, the compression strength with WBP contents up to 15% is superior to that without WBP, while the compression strength decreases with WBP incorporation when the WBP fineness is close to or lower than the cement fineness. Incorporating an appropriate WBP content decreases the water absorption of mortar, and the water absorption further decreases with increasing WBP fineness; for example, when the median diameter of WBP is 6 μm and 42 μm, the capillary absorption coefficient of mortar with 30% WBP is 34.1% lower and 10.3% higher than that of plain mortar, respectively. In addition, a similar conclusion is observed for the water distribution in WBP mortar.